2015
DOI: 10.3832/ifor1150-007
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale spatial genetic structure in a multi-oak-species (Quercus spp.) forest

Abstract: © iForest -Biogeosciences and Forestry © SISEF http://www.sisef.it/iforest/ 324 iForest (2015) 8: 324-332 Citation: Curtu AL, Craciunesc I, Enescu CM, Vidalis A, Sofletea N, 2015. Fine-scale spatial genetic structure in a multi-oak-species (Quercus spp.) forest. iForest 8: 324-332 [online 2014-09-05]Patterns of fine-scale spatial distribution of multilocus genotypes can provide valuable insights into the biology of forest tree species. Here we tested for the existence of spatial genetic structure (SGS) in a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…Nevertheless, the levels of population genetic parameters found in our study were similar to those observed by other authors (Streiff et al, 1998;Cottrell et al, 2003;Curtu et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, the levels of population genetic parameters found in our study were similar to those observed by other authors (Streiff et al, 1998;Cottrell et al, 2003;Curtu et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…In the case of oaks, the recently proposed validated multiplexes of microsatellites were used mostly to study mating patterns (Lagache et al, 2014), interspecific hybridization processes (Lander et al, 2013) or species identification (Neophytou, 2013;Rellstab et al, 2016) rather than genetic diversity (Curtu et al, 2015;Moracho et al, 2016). Nevertheless, the levels of population genetic parameters found in our study were similar to those observed by other authors (Streiff et al, 1998;Cottrell et al, 2003;Curtu et al, 2015).…”
Section: Discussionsupporting
confidence: 74%
“…Commonly (e.g. Chamaecrista fasciculata (Fenster 1991), Heliconia acuminata (Cortes et al 2013)), higher gene dispersal distances tend to be found in low-density populations (Vekemans and Hardy 2004), although in mixed stands high tree density may limit dispersal by serving as a physical barrier to the movements of propagules (Curtu et al 2015). Our estimated gene dispersal distance was 103 m in Guba-Arenja and 124 m in the denser population in Kurmuk.…”
Section: Fine-scale Spatial Genetic Structurementioning
confidence: 72%
“…The balance achieved by a population among these factors determines its special genetic structure (Valencia-Cuevas et al, 2014). Genetic structure can be associated with geographical region, climate conditions (Neophytou et al, 2010), hybridization (Curtu et al, 2014), breaking of primary reproductive barriers (Valencia-Cuevas et al, 2014), altitude, historical movements, evolution, phenology and seed dispersal over a large area by animals (Ohsawa et al, 2007;Zhang et al, 2013 andWang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%